Pengalaman Emosional Pasien Post Pengobatan TB MDR - Agnes Anrilia Natro; Desi Desi; Fiane de Fretes (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: Describe the emotional experiences of patients after MDR TB Treatments.Methods: Qualitative descriptive with three participants. The data from the interviews were analyzed through a process of data reduction and grouping of themes.Results: Participants in this study had positive and negative emotional experiences. Positive experiences such as sincerity, patience during and after treatment, also participants expect that the disease does not recur and not be transmitted to other people. While the negative experience is that participants appear pensive more often, rarely leave the house and even limit themselves to the environment, low self-esteem and self-acceptance. This emotional experience is influenced by several factors such as participants' knowledge of the disease treatment process, side effects of drugs that cause low self-esteem behavior and the support system and motivation they have for the treatment process being undertaken. Conclusion: Participants in the study experienced positive and negative emotions during treatment even until treatment was completed.